Coil Embolization of a Palatine Artery Pseudoaneurysm in a Gelding. Issue 4 (5th April 2014) - McClellan, Nathaniel R.; Mudge, Margaret C.; Scansen, Brian A.; Jung, Stephen S.; Russell, Duncan
<x xml:space="preserve">Abstract</x> Objective To describe successful transarterial coil embolization of a palatine artery pseudoaneurysm that extended into the caudal maxillary sinus of a gelding. Study Design Clinical report. Animal A 24‐year‐old Morgan gelding with right‐sided epistaxis. Methods The right maxillary sinus was imaged by radiography, computed tomography, and sinoscopy. Angiography was performed to locate the source of bleeding, and transarterial coil embolization of a right palatine artery pseudoaneurysm was performed. Results There was some mucoid nasal discharge and an intermittent cough postoperatively. No epistaxis was seen after embolization. There was moderate swelling of the surgical incision over the mid‐cervical common carotid artery. The horse was discharged from the hospital 4 days after surgery, and had been doing well, with no signs of bleeding, for 2 months postoperatively. The horse had acute colic secondary to a strangulating lipoma at 2 months and was euthanatized after exploratory celiotomy. Placement of embolization coils in the right palatine artery was confirmed by CT and necropsy. Conclusions Severe epistaxis in the horse may be caused by a ruptured major palatine artery pseudoaneurysm. Occlusion of this vessel can be successfully accomplished by transarterial coil embolization.